University reserves management: international practices and opportunities for Lithuania - Černiauskas, Gediminas; Seiranov, Jusif (Business, Management and Economics Engineering, 2011)
The article considers the new opportunities for university reserves management arising in the process of transition to non-profit institution model in Lithuania. Authors review historical background of university funding and significance of endowments. The role of endowments in leading USA and UK universities is analyzed. Structural differences and common trends in the mix of public and private funding of higher education in different countries are showed. Authors analyse the transition from budgetary to nonprofit institution in higher education in Lithuania since 2009 and suggest practical approach to university reserve creation, funds management and financial endowment build-up in the new institutional framework of higher education in Lithuania.